Pembuatan Plastik Biodegradable dari Limbah Kulit Pisang Raja Dengan Gliserol dan Minyak Sereh - Aulia Rahmad Lubis; Muhammad Irsyad Mahadi Lubis; Cut Meurah Rosnelly (Jurnal Inovasi Ramah Lingkungan, 2020)
The use of plastic as a packaging is increasing, cause the stacking of plastic waste. It has an impact on environmental pollution, because plastic waste is a difficult waste to be decomposed by microorganism. Various attempts have been done to solve the problem of plastic waste, either is to make environmentally friendly plastic (bioplastic). Bioplastic is a plastic can be degraded by microorganism from source of plant compounds, such as cellulose and lignin. Banana peel can be used as raw material in the manufacture of bioplastic, because it has high content. Manufacture of environmentally friendly bioplastic packaging is done by the casting method. The problem is the mechanical properties of bioplastic is not similar to conventional plastic. Thus, various studies with variation of glycerol plasticizer concentration 20, 30 and 40% and with addition of antimicrobial lemongrass oil with concentration 10, 20 and 30%. The best result were obtained at 20% glycerol concentration with a tensile strength value of  0,415 kgf/mm 2 , and for the best elongation percentage in glycerol concentration and 40-10% lemongrass oil of 58,3% and water absorption also found in glycerol and concentration lemongrass oil 40-10% of 244%. For biodegradation test, the highest concentration of lemongrass oil was 30% with a degradation period of 22 days. In functional group testing with FT-IR showed a bioplastic sample added with lemongrass oil contained eight functional group and without lemongrass oil having five functional group, which the only difference in the range 2113,98 with the C=C alkuna group and in the range 1645,28 with the alkena group C=C.